2021
DOI: 10.1002/jso.26426
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patient‐reported outcome measures following limb salvage with complex reconstruction or amputation in the treatment of upper extremity sarcoma

Abstract: Background and Objectives This study compares long‐term patient‐reported outcomes between patients that underwent limb‐salvage surgery with complex reconstruction by free or pedicled flap (LS) or amputation. Additionally, the need for revision surgery is compared. Methods A total of 43 patients were studied at a median follow‐up of 9.54 years. Sixteen patients completed questionnaires regarding functional outcome and mental wellbeing. Functional outcomes were measured by using the Toronto Extremity Salvage Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Several small samples or single-center clinical cohort studies have shown that LSS had a better prognosis than amputation among patients with EBST sarcomas ( 13 , 29 ). In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ). Some studies have reported no significant difference in the incidence of local recurrence of sarcoma among patients who underwent LSS and amputation ( 8 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several small samples or single-center clinical cohort studies have shown that LSS had a better prognosis than amputation among patients with EBST sarcomas ( 13 , 29 ). In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ). Some studies have reported no significant difference in the incidence of local recurrence of sarcoma among patients who underwent LSS and amputation ( 8 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a cohort of 43 sarcoma patients, Yannick et al. ( 10 ) reported comparable mental wellbeing between patients with LSS and those receiving amputation, although the functional benefits of LSS over amputation were maintained at nearly 10 years of follow-up. However, we could not evaluate the impact of LSS on the quality of life in these patients in detail using data from the SEER program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 2 Furthermore, they contributed to the improvement in quality of life of sarcoma patients, as limbs that previously required amputation could now be salvaged. 3 The anterolateral thigh (ALT) flap is a well-established soft tissue perforator flap usually supplied by the descending branch of the lateral circumflex femoral vessels. 4 Compared with the anteromedial thigh flap, it is thinner and the harvesting process is straightforward.…”
mentioning
confidence: 99%